Life orthogonal. (23rd December 2021) - Handal-Marquez, Paola; Pinheiro, Vitor B.
Abstract : It is surprisingly common for us to think that we are the apex of evolution. Similarly, it is easy to convince ourselves that after nearly 3bn years, life on Earth has tried everything: every possible chemical reaction, every possible solution and every possible arrangement. Fortunately, both statements are wrong. We now know that the DNA (and RNA) life on Earth is one solution, of many, on how chemistry can turn towards life. As we discover new ways to code genetic information, in what is an interdisciplinary basic science endeavour, we develop many of the technologies that will establish significant biotechnological and life-saving applications. Welcome to life orthogonal.